(untitled) (International Journal of Economics Management and Social Science, 2026)
Background: The expansion of extractive capitalism across the Global South has intensified conflicts over natural resources, disproportionately affecting indigenous and local communities whose livelihoods, cultures, and territorial rights are embedded in the ecosystems being exploited. Objective: This study analyzes the dialectical relationship between extractive capitalism, ecological conflict, and indigenous community resistance through the theoretical lens of political ecology and environmental justice. Methods: A systematic literature review was conducted using peer-reviewed articles, reports, and theoretical texts published between 2019 and 2025, sourced from Scopus, Web of Science, and Google Scholar. Search terms included political ecology, extractive capitalism, indigenous resistance, environmental justice, green grabbing, and resource conflict. Results: The review reveals that extractive capitalism operates through dispossession mechanisms—including land grabbing, green grabbing, and territorial enclosure—that systematically marginalize indigenous communities. Resistance takes multiple forms, including legal advocacy, territorial defense, international networking, and the reassertion of traditional ecological governance. Environmental justice frameworks provide the normative basis for these struggles. Conclusion: Political ecology offers a robust analytical framework for understanding resource conflicts as expressions of broader structural inequalities, and indigenous resistance movements are best understood as dialectical responses to capitalist accumulation by dispossession. Strengthening indigenous rights frameworks and environmental justice institutions is essential to sustainable and equitable resource governance. Keywords: political ecology, extractive capitalism, indigenous resistance, environmental justice, accumulation by dispossession, social ecology, resource conflict